Multi-mode optical coded patterns enabled by upconversion nanoparticles and photonic crystals. (27th September 2019) - Zhang, Hanbing; Xu, Linlin; Liu, Fenchao; Huang, Chao; Wei, Jie
Abstract: In this study, we designed the luminescent enhanced composites by combining upconversion nanoparticles (UCNPs) and photonic crystals (PCs), and prepared multi-mode coding patterns through utilizing the optical properties of both materials, respectively. We prepared UCNPs with different luminescence and the composite materials can be quickly obtained by spin-coating the UCNPs on the surface of the PCs. We discover that the composite materials have significant luminescent enhancement and the enhancement of upconversion is attributed to the Bragg reflection of the photonic band gap. We fabricated upconversion luminescent lattices based on the surface of the PCs by dropping and endowed with the meaning of the Morse code so that it can have more information in different modes. In addition, we further obtained the cipher table pattern according to the structural color of the PCs and the luminescence of the UCNPs. The results reveal great potential applications in the field of multi-mode optical imaging and anti-counterfeiting.